Graphene-based nanocomposites: synthesis and their theranostic applications. (26th November 2018) - Madni, Asadullah; Noreen, Sobia; Maqbool, Irsah; Rehman, Faizza; Batool, Amna; Kashif, Prince Muhammad; Rehman, Mubashar; Tahir, Nayab; Khan, Muhammad Imran
Abstract: Graphene, the mother of all carbon materials, has unlocked a new era of biomedical nanomaterials due to its exceptional biocompatibility, physicochemical and mechanical properties. It is a single atom thick, nanosized, two-dimensional structure and provides high surface area with adjustable surface chemistry to form hybrids. The present article provides a comprehensive review of ever-expanding application of graphene nanomaterials with different inorganic and organic materials in drug delivery and theranostics. Methods of preparation of nanomaterials are elaborated and biological and physicochemical characteristics of biomedical relevance are also discussed. Graphene form nanomaterials with metallic nanoparticles offer multiscale application. First, graphene act as a platform to attach nanoparticles and provide excellent mechanical strength. Second, graphene improves efficacy of metallic nanoparticles in diagnostic, biosensing, therapeutic and drug delivery application. Graphene-based polymeric nanocomposites find wider application in drug delivery with flexibility to incorporate hydrophilic, hydrophobic, sensitive and macromolecules. In addition, grapheme quantum dots and graphene hybrids with inorganic nanocrystal and carbon nanotubes hybrids have shown interesting properties for diagnosis and therapy. Finally, we have pointed out research trends that may be more common in future for graphene-based nanomaterials.